HYDRAULIC TRANSIENT CONTROL OF REFURBISHED FRANCIS TURBINE HYDROPOWER SCHEMES IN SLOVENIA - Mazij, Jernej; Bergant, Anton (Journal of Energy Technology, 2024)
This paper presents hydraulic transient control methods of refurbished Francis turbine hydropower schemes in Slovenia. Transient control strategies are presented, including the alteration of operational manoeuvres, transient control devices, suitable water conveyance system layout and operational limits. Computational models and modern hydraulic transient control approaches are also outlined. The paper concludes with the practical implementation of two case studies: the refurbish ment of Moste HPP and Doblar 1 HPP. Both hydropower plants are equipped with Francis turbine units and underwent refurbishment in 2010 to 2013, respectively.